A Test Of Ecoenzymes And Liquid Organic Fertilizer Waste Coconut Water On Growth And Production Green Beans (Vigna Radiata) - Fitri Melinia Nasution; Sulardi, Sulardi; Muhammad Wasito (Jurnal Scientia, 2024)
The aim of this research is to determine the response of applying multifunctional fertilizer and organic coconut water fertilizer to the growth and production of Mung Bean (Phaseolus radiatus.) plants and their interactions. This paper was carried out in Klambir Lima Hamparan Perak Village, Deli Serdang Regency, North Sumatra from January to March 2024, using a factorial Randomized Block Design (RAK), with two blocks, 16 combinations. Factor I: Coconut water 4 practices A0= 0 ml/liter of water, A1= 50 ml/liter of water; A2= 100 ml / liter of water; A3= 150 ml / liter of water; Factor II: Ecoenzyme administration with 4 levels, namely: E0 = No Ecoenzyme administration (0 ml/liter of water); E1= 5 ml/liter of water; E2= 10 ml/liter of water; E3= 15 ml/liter of water. Parameters observed: 1. Plant height (cm), 2. Number of productive branches, 3. Number of pods per sample, 4. Weight of pods per plot, 5. Weight of 100 seeds and 6. Production per plot. The results of observations on the coconut water treatment showed that the parameters Plant Height, Number of Pods per sample, Number of Branches per sample showed very real results, but the parameter Weight of 100 seeds did not show a significant difference, while the interaction between giving Coconut Water and Ecoenzymes had no real effect on all observed parameters.